The Influence of Competency and Talent Management on Career Growth Opportunities Through Work Ethic - Kristina Sedyastuti; Dedi Rianto Rahadi; Dianawati Suryaningtyas (Fundamental and Applied Management Journal, 2026)
This study examines the impact of working ethics on career development opportunities through competency and talent management in PT Ikhlas's work environment. In this study, the quantitative approach has been applied, with a sample size of 215 respondents, and simple random sampling to obtain information on PT Ikhlas employees. The technique used to analyze data is SEMPLS and the Smart PLS 4.0.9.6 software has been adapted for this purpose. The results of the study revealed that competence has a positive and negligible impact on work ethic, talent is very important in terms of job ethics, competencies are extremely beneficial when it comes to career growth opportunities, managerial skills have a favorable and negative effect on careers, work ethic has a positive and negligible effect on career growth opportunities, competence has a positive and negligible effect on career growth opportunities through work ethic, talent management has a significant positive effect on career growth opportunities through work ethic. Companies can optimize their career development strategies to improve employee productivity and welfare when they understand the relationship between competence, talent management as well and work ethics.